Biodesulfurization of dibenzothiophene by Shewanella putrefaciens NCIMB 8768 - Ansari, Farahnaz; Prayuenyong, P.; Tothill, Ibtisam E. (Cranfield University, 2007)
The desulfurization ability of Shewanella putrefaciens strain NCIMB 8768 was studied and its activity profile was compared with the widely studied strain Rhodococcus erythropolis strain IGTS8. Dibenzothiophene (DBT) is a recalcitrant thiophenic component of fossil fuels especially among diesel blend stocks. DBT in basic salt medium (BSM) at a final concentration of 0.3, 0.6 and 0.9 mM was supplied to the microbes as the sole sulfur source. Experimental results showed that S. putrefaciens, similar to other biodesulfurization organisms, converted DBT to the end product 2-hydroxybiphenyl (HBP), as detected by the Gibbs assay and HPLC. Cells cultivated in medium containing 0.3 mM of DBT showed the highest desulfurization activity, with a maximum specific production rate 43.5 mmol/L of HBP.
Keywords: Biodesulfurization; Dibenzothiophene; Shewanella putrefaciens